2018
DOI: 10.1177/2398212818771821
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of disordered dialogue: Prefrontal, hippocampal and thalamic miscommunication underlying working memory deficits in schizophrenia

Abstract: The prefrontal cortex is central to the orchestrated brain network communication that gives rise to working memory and other cognitive functions. Accordingly, working memory deficits in schizophrenia are increasingly thought to derive from prefrontal cortex dysfunction coupled with broader network disconnectivity. How the prefrontal cortex dynamically communicates with its distal network partners to support working memory and how this communication is disrupted in individuals with schizophrenia remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 313 publications
(414 reference statements)
0
30
0
Order By: Relevance
“…Recent rodent studies have similarly indicated circuit abnormalities underlying and resulting from thalamic dysfunction (108). The thalamus is composed of multiple nuclei, each with their distinct afferent and efferent projections (109).…”
Section: Thalamic Nuclei and Regulation Of The Da Systemmentioning
confidence: 99%
“…Recent rodent studies have similarly indicated circuit abnormalities underlying and resulting from thalamic dysfunction (108). The thalamus is composed of multiple nuclei, each with their distinct afferent and efferent projections (109).…”
Section: Thalamic Nuclei and Regulation Of The Da Systemmentioning
confidence: 99%
“…Abnormal prefrontal-hippocampal coupling during the tasks has been described in schizophrenia patients 4,6 . It relates not only to local alterations at microscopic and macroscopic scales in both areas 7 but also to connectivity dysfunction within large-scale networks 8 . In particular, the interactions between HP and entorhinal cortex, which tightly communicate with each other along reciprocal pathways 9 , have been tackled in clinical and neuropathological investigations 10,11,12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the memory maintenance phase, the direction of information ow is from the hippocampus to mPFC, while during the memory retrieval phase, the direction is from the mPFC to hippocampus (Dolleman-van et al, 2019;Eichenbaum, 2017). In recent years, studies have demonstrated that the mPFC exist mutual connectivity and communication with the hippocampus and mediodorsal thalamus and are essential for maintaining working memory (Bolkan et al, 2017;Kupferschmidt and Gordon, 2018;Parnaudeau et al, 2018;Schmitt et al, 2017). In the mediodorsal thalamus, there are glutamatergic thalamocortical neurons and GABAergic interneurons (Kuroda et al, 1998;Tiwari et al, 2013) that receive projection from mPFC neurons and then drive mPFC activity to integrate signals for adaptive goal-directed behavior (Miller et al, 2017).…”
Section: The Neural Circuit Of Hippocampus-mediodorsal Thalamus-mpfcmentioning
confidence: 99%